GEOCMS: TOWARDS A GEO-TAGGED MEDIA MANAGEMENT SYSTEM - J. Y. Park; Y.-H. Jung; W. Ding; K. W. Nam (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2019)
In this paper, we propose the design and implementation of the new geo-tagged media management system. A large amount of daily geo-tagged media data generated by user’s smart phone, mobile device, dash cam and camera. Geo-tagged media, such as geovideos and geophotos, can be captured with spatial temporal information such as time, location, visible area, camera direction, moving direction and visible distance information. Due to the increase in geo-tagged multimedia data, the researches for efficient managing and mining geo-tagged multimedia are newly expected to be a new area in database and data mining. This paper proposes a geotagged media management system, so called Open GeoCMS (Geo-tagged media Contents Management System). Open GeoCMS is a new framework to manage geo-tagged media data on the web. Our framework supports various types which are for moving point, moving photo – a sequence of photos by a drone, moving double and moving video. Also, GeoCMS has the label viewer and editor system for photos and videos. The Open GeoCMS have been developed as an open source system.